Tawakal and Endeavors from the Perspective of Qadariyah and Jabariyah Thoughts Responding to the Covid 19 Pandemic - Surni Kadir (Universitas Muhammadiyah Palu, 2023)
The Covid-19 outbreak is developing so fast in the midst of the life of the world community, and Indonesia is no exception. Its presence causes panic that is so terrible, because of the threat that is not kidding, which can lead to death. All lines take a role to be able to stop the rate of development of the effects of this virus, to stop crowd activities, including worship in houses of worship. With this policy, the community's response varied greatly. Of course this response is the result of the understanding that has been carried out so far. There are three groups in addressing the issue of destiny. First, Jabariyah is a group that only puts their trust in Allah, but denies endeavor. Second, the Qadariyyah are a group that denies destiny, only make endeavors but forget to rely on Allah. The third is the middle group, namely the group that is able to combine the concept of trustworthiness with endeavor in matters of destiny. So to provide a bright spot and be able to understand the problem of destiny, this situation needs to be described, then given a conceptual analysis related to the problem of destiny in the perspective of Qadariyah, Jabariyah and the concepts of endeavor and trust.